1972
DOI: 10.1007/bf02533022
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac lipids in rats and gerbils fed oils containing C22 fatty acids

Abstract: Docosenoic acid from rapeseed oil or herring oil in the diet of the young rat promoted an accumulation of cardiac lipid. The triglyceride fraction accounted for most of the deposited fat and contained a high concentration of the docosenoic acid. Liquid rapeseed oil, partially hydrogenated rapeseed oil or partially hydrogenated herring oil increased the amount of cardiac fatty acids at 1 week and led to the development of degenerative lesions at 16 weeks. Whale or seal oils low in C22 fatty acids produced littl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
37
0
1

Year Published

1973
1973
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(43 citation statements)
references
References 14 publications
5
37
0
1
Order By: Relevance
“…These acids might prove to be the factors responsible for the poor growth performance and patho logical effects observed in animals fed some marine oils [8,[21][22][23],…”
Section: Discussionmentioning
confidence: 99%
“…These acids might prove to be the factors responsible for the poor growth performance and patho logical effects observed in animals fed some marine oils [8,[21][22][23],…”
Section: Discussionmentioning
confidence: 99%
“…9 Further, high consumption of erucic acid may increase concentration of adrenal cholesterol, cause fibrotic changes in myocardium, and increase liver weight and cholesterol. 10,11 Palm oil is widely used in food applications, providing various fractions after the winterization process in which palm stearin (PS), one of the fractions, is mainly composed of high-melting triacylglycerides. 12 The purpose of this study was to develop solid fat from MO and PS through a lipase-catalyzed reaction, in which linoleic acid (LA) was intentionally incorporated owing to its beneficial health effects.…”
Section: Introductionmentioning
confidence: 99%
“…8 It has been shown in experimental animals that high intake of this type of oil may increase the content of adrenal cholesterol, may interfere with reproduction, cause fibrotic changes in myocardium and increase liver weight and liver cholesterol. 9,10 Metabolic studies have been conducted on Indian subjects to investigate the effects of using fish oils and linolenic acid (18:3 n-3) rich oils (canola oil and high erucic mustard oil) in comparison with oils those contain negligible amounts of linolenic acid (18:3) (groundnut oil and palmolein), on plasma lipids, essential fatty acid status and platelet aggregation. The results showed that at a level of 6-7 energy % linoleic (18:2 n-6), about 0.20-0.50 energy % fish oils or 1.40 energy % linolenic acid produced antiatherogenic effects.…”
Section: Introductionmentioning
confidence: 99%